The exploitation of heath forest species as potential natural herbicides for weed management - Othman, Rashidi; Wan Daud, Wan Masyitah; Ramya, Razanah; Mat Ali, Qurratu Aini (Nova Science Publishers, Inc., 2024)
Weeds exhibit diverse habits and inhabit various environments globally. Within the realm of landscape management, the presence of weeds is a concern due to their competition with other plants for essential growth factors. Contemporary weed management heavily relies on synthetic chemicals to regulate these undesirable plants, aiming to minimise associated costs. However, the usage of herbicides is not always an ideal solution, as it can have detrimental effects on the environment. Effective landscape and natural resource management go beyond creating pleasing aesthetics; it involves continuous enhancement and preservation. This study specifically investigates heath forest species as promising candidates for natural herbicides in weed management. The focus of the research is on exploring the allelopathic properties of certain plants (Melaleuca cajuputi) from heath forest ecosystems as potential agents for sustainable landscape maintenance. In order to evaluate the efficacy of M. cajuputi as a weed control agent, phenolic acid components present in M. cajuputi leaves were evaluated against Glossostigma elatinoides. The allelochemical efficacy of this model system was evaluated over a period of four weeks, utilising three distinct concentrations and four distinct time intervals to control the growth of weeds. Overall, the research’s findings point to the effectiveness, economic viability, and environmental friendliness of using allelopathy plant species as bioherbicides to treat weeds. Additionally, it confirmed that the use of plants is more environmentally friendly and has a great chance of being used to improve the quality of the environment’s health. The findings suggest that the effectiveness of utilising phenolic compounds as herbicidal agents for weed control depends on various aspects, including plant attributes, allelopathic interaction mechanisms, and ecological conditions. Consequently, there is a need for further exploration into these aspects.